Neuropsychological outcomes of coronary artery bypass grafting - Nafisa Cassimjee; Caroline L Couzens; Frans J Smith; Claire Wagner (AOSIS, 2004)
People with coronary heart disease have recourse to a palliative intervention such as Coronary Artery Bypass Grafting (CABG). Opsomming Persone met 'n koronêre hartsiekte is soms genoodsaak om 'n hartomleiding (CABG), wat 'n tydelike intervensie ter verligting is, te ondergaan. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.